SIFAT PEMESINAN 34 JENIS KAYU DARI MALUKU & SULAWESI TENGAH - Osly Rachman; Jamal Balfas (Pusat Penelitian dan Pengembangan Hasil Hutan, 1985)
The machining properties of 34 wood species tested according to the ASTMD 1666-64 procedure are presented in this paper. The machining properties studied were planing, shaping, turning, sanding, boring and mortising.Some of the species tested (such as suling, gohimahou etc.) are consistently better than average in most respects and some are consistently poorer (such as telor, andolia etc.). Some are good in one property or two and poor in others. These differences are probably due to differences in the specific gravity values of each species